2021
DOI: 10.17146/jpen.2021.23.2.6536
|View full text |Cite
|
Sign up to set email alerts
|

Korelasi Antara Kecepatan Gelombang Geser dan NSPT di Area Pulau Nuklir, Tapak RDE Serpong

Abstract: Karakteristik gerakan tanah akibat gempabumi dipengaruhi oleh variasi nilai kecepatan gelombang geser (Vs). Ketersediaan nilai Vs suatu daerah belum tentu lengkap dan siap, hal ini disebabkan oleh penyelidikan langsung guna memperoleh nilai Vs memerlukan waktu relatif lama dan biaya yang tidak sedikit. Selain itu juga dipengaruhi oleh tingkat keterjangkauan suatu daerah pengujian. Berbeda halnya dengan data jumlah pukulan (N) dari uji Standard Penetration Test (NSPT) yang lebih banyak tersedia. Dewasa ini tela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The V S profile from microtremor array data SPAC method processing and the HVSR curve is shown in Figure 8. The SPAC V S results referenced the previous study (Iswanto et al, 2020). The G5 SPAC analysis result showed that the upper layer consisted of soil layers with V S values ranging from 90 m/s to 300 m/s.…”
Section: Spac Data Analysis Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The V S profile from microtremor array data SPAC method processing and the HVSR curve is shown in Figure 8. The SPAC V S results referenced the previous study (Iswanto et al, 2020). The G5 SPAC analysis result showed that the upper layer consisted of soil layers with V S values ranging from 90 m/s to 300 m/s.…”
Section: Spac Data Analysis Resultssupporting
confidence: 77%
“…This study also used two microtremor array data, SPAC G5 and G6, published by Iswanto et al (2020). The microtremor array points were located in the Pantai Gosong coast area, as shown in Figure 2.…”
Section: Microtremor Datamentioning
confidence: 99%